Developmental capacity is unevenly distributed among single blastomeres of 2-cell and 4-cell stage mouse embryos - Katarzyna Krawczyk (Nature Portfolio, 2021)
Abstract During preimplantation development, mammalian embryo cells (blastomeres) cleave, gradually losing their potencies and differentiating into three primary cell lineages: epiblast (EPI), trophectoderm (TE), and primitive endoderm (PE). The exact moment at which cells begin to vary in their potency for multilineage differentiation still remains unknown. We sought to answer the question of whether single cells isolated from 2- and 4-cell embryos differ in their ability to generate the progenitors and cells of blastocyst lineages. We revealed that twins were often able to develop into blastocysts containing inner cell masses (ICMs) with PE and EPI cells. Despite their capacity to create a blastocyst, the twins differed in their ability to produce EPI, PE, and TE cell lineages. In contrast, quadruplets rarely formed normal blastocysts, but instead developed into blastocysts with ICMs composed of only one cell lineage or completely devoid of an ICM altogether. We also showed that quadruplets have unequal capacities to differentiate into TE, PE, and EPI lineages. These findings could explain the difficulty of creating monozygotic twins and quadruplets from 2- and 4-cell stage mouse embryos.